Illegal Leisure Revisited : Changing Patterns of Alcohol and Drug Use in Adolescents and Young Adults. - Aldridge, Judith (Taylor & Francis, 2011)
This book updates the progress into adulthood of the cohort of fourteen-year-olds who were recruited and tracked until they were eighteen years old. Illegal Leisure (1998) described their adolescent journeys and lifestyles, focusing on their early regular drinking and extensive 'recreational' drug use. This new edition revisits these original chapters, providing commentaries around them to discuss current implications of the original publication, plus documenting and discussing the group at twenty-two and twenty-seven years of age. Illegal Leisure Revisited positions the journeys of these twent.